CHINA'S CULTURAL DIPLOMACY AND ITS ENGAGEMENT WITH THE PERANAKAN COMMUNITY IN MALACCA - Kornphetcharat, Kotchaphop; Thien, Lee Yuen (UI Scholars Hub, 2025)
China's cultural diplomacy utilizes a range of strategies, including cultural exchange programs, media outreach, and people-to-people interactions, to further its national interests and enhance its international image. The primary aims are to foster a positive perception of China, build mutual understanding and trust with other nations, and expand China's cultural and economic influence. The overseas Chinese community in Southeast Asia has been recognized as a crucial conduit for advancing Chinese cultural policy globally. Recently, the Chinese government has conducted official visits to the Baba & Nyonya Heritage Museum in Malacca, Malaysia, exemplifying its efforts to engage with the local community. This research article explores China's engagement with Southeast Asia through cultural heritage, with a particular focus on the Peranakan community in Malaysia as a case study.